2012
DOI: 10.1186/1476-0711-11-20
|View full text |Cite
|
Sign up to set email alerts
|

Biological activities of extracts from Chenopodium ambrosioides Lineu and Kielmeyera neglecta Saddi

Abstract: BackgroundChenopodium ambrosioides and Kielmeyera neglecta are plants traditionally used in Brazil to treat various infectious diseases. The study of the biological activities of these plants is of great importance for the detection of biologically active compounds.MethodsExtracts from these plants were extracted with hexane (Hex), dichloromethane (DCM), ethyl acetate (EtOAc) and ethanol (EtOH) and assessed for their antimicrobial properties, bioactivity against Artemia salina Leach and antifungal action on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 40 publications
3
18
1
Order By: Relevance
“…Chenopodium ambrosioides Linn (Amaranthaceae), popularly known as "mastruz" and widely used in folk medicine, being considered one of the plant species with potential for use in the production chain and to generate products of interest to the Brazilian Unified Health [47]. It is an annual or perennial herbaceous plant with distinctive aroma, upright, that reaches up to 1.5 m high, with dark green and camphorated pubescent leaves.…”
Section: Introductionmentioning
confidence: 99%
“…Chenopodium ambrosioides Linn (Amaranthaceae), popularly known as "mastruz" and widely used in folk medicine, being considered one of the plant species with potential for use in the production chain and to generate products of interest to the Brazilian Unified Health [47]. It is an annual or perennial herbaceous plant with distinctive aroma, upright, that reaches up to 1.5 m high, with dark green and camphorated pubescent leaves.…”
Section: Introductionmentioning
confidence: 99%
“…For a long time C. ambrosioides was used traditionally for solving many health problems i.e., inflammation, diabetes, parasites, cough, typhoid, and influenza 14,15 . Reviewing the literature revealed that the different parts of C. ambrosioides showed numerous biological activities i.e., antimicrobial 16,17 , cytotoxicity 18 , antioxidant 19 , larvicidal 20 , antidiabetic 4 , antiparasitic 21 , antiviral 22 , and molluscidal 23 . Moreover, from the phytochemistry point of view C. ambrosioides is known to contain secondary metabolites i.e., saponins 24 , terpenoids 2,25,26 , flavonol glycosides 27,28 , flavone glycosides 29 , and chenopodiumamines & chenopodiumoside 30 .…”
Section: Introductionmentioning
confidence: 99%
“…The main source is to be found in plants. Many plant extracts have biological activity both in vitro and in vivo [31]. Difference of susceptibility to fluconazole and E. cephalotes may be due to the indiscriminate use of fluconazol in patients with vulvovaginit candidiasis.…”
Section: Discussionmentioning
confidence: 99%